Kajian Aspek Perilaku Pada Ruang Kerja Dosen Arsitektur - Dela Andriani; Soraya Masthura Hassan; Erna Muliana (Universitas Syiah Kuala, 2022)
Work is a human activity to achieve the fulfillment of their needs. There are various kinds of work fields according to their expertise and specificity, one of which is a lecturer who teaches at the higher education level. Lecturers carry out their duties independently when working. All his teaching, research, and service work is done independently. Therefore, lecturers need a particular room to accommodate the three activities.Meanwhile, the available space is not maximized and leads to crowds. This research is qualitative research with a case study approach. The research location is in Lhokseumawe, precisely in the lecturer room of the Architecture Study Program, Faculty of Engineering, Malikussaleh University. The research method used is the participatory observation technique and behavior mapping. The results of this research are directed to architectural development, especially in the scope of the locus itself.